Pelayanan E-Service dalam Pembayaran Pajak BPHTB di BPPKAD Kabupaten Wonosobo - Jasterik Pamuji Yanto; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Digital-based public services have become one of the government strategies to improve effectiveness, efficiency, and transparency in public service delivery, including regional taxation services. One form of this transformation is the implementation of e-service in Duty on Acquisition of Land and Building Rights (BPHTB) payment services at BPPKAD Wonosobo Regency.This study aims to describe the implementation of BPHTB e-service , analyze service quality based on the E-SERVQUAL model, identify supporting and inhibiting factors, and development initiatives at BPPKAD Kabupaten Wonosobo. This study employed a descriptive qualitative approach using a case study design. Data were collected through observation, semi structured interviews, and documentation involving purposively selected informants. Data analysis referred to the Miles and Huberman interactive model.The findings indicate that the implementation of BPHTB e-service has improved public service quality. Based on E SERVQUAL dimensions, efficiency improved service speed and convenience; fulfillment showed that service needs were accommodated; system availability indicated relatively stable service operation; and privacy demonstrated protection of user data. However, challenges remain regarding human resources, budget limitations, and public digital literacy.